Early infantile‐onset epileptic encephalopathy 28 due to a homozygous microdeletion involving the WWOX gene in a region of uniparental disomy. Issue 1 (18th November 2018) - Davids, Mariska; Markello, Thomas; Wolfe, Lynne A.; Chepa‐Lotrea, Xenia; Tifft, Cynthia J.; Gahl, William A.; Malicdan, May Christine V.
Abstract: The genetic etiologies of many rare disorders, including early infantile epileptic encephalopathies, are largely undiagnosed. A 6‐year‐old girl was admitted to the National Institutes of Health Undiagnosed Diseases Program with profound intellectual disability, infantile‐onset seizures, chronic respiratory failure, facial dysmorphisms, skeletal abnormalities, and atrial septum defect. A large region of homozygosity was discovered on chromosome 16, spanning 16q22.1–16q24.3' caused by uniparental disomy (UPD) that included a maternally inherited homozygous microdeletion covering exon 6 of WWOX (NM_016373.3). mRNA expression analysis revealed that the deletion led to nonsense‐mediated decay of the NM_016373.3 transcript; the exon 6 of an alternative transcript (NM_130791.3), lacking the short‐chain dehydrogenase, was utilized. The microdeletion in WWOX explains the seizures and intellectual disability, while pathogenic variants in another gene, HSPG2, are likely responsible for the patient's skeletal abnormalities. This report describes a rare autosomal recessive disorder with multiple genetic etiologies, one of which involves UPD. Abstract : This report describes a rare autosomal recessive disorder with multiple genetic etiologies, one that involves uniparental disomy. A 6‐year‐old girl was admitted to the NIH Undiagnosed Diseases Program with profound intellectual disability, infantile‐onset seizures, facial dysmorphisms, and skeletal abnormalities. Chromosome 16q22.1–16q24.3 uniparental disomy, included a maternally inherited homozygous microdeletion covering exon 6 of WWOX (NM_016373.3), which could cause the seizures and intellectual disability. Additional pathogenic compound heterozygous variants in HSPG2 are likely responsible for the patient's skeletal abnormalities.